THE RELATIONSHIP OF NURSES' THERAPEUTIC COMMUNICATION IN THE WORK PHASE AND PATIENTS' SATISFACTION WITH NURSING SERVICES IN THE HOSPITAL INPATIENT ROOM DR. Drs. M. HATTA BUKITTINGGI - Hayulita, Sri; Andriani, Marlina; Rahmi Sapitri, Elshama (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
One the factors that influence patient satisfaction is the communication that exists between health workers and patients, if the nurse does not provide good theraupetic communication it will cause the patient and family to feel dissatisfied. Communication plays an important role in running the health service process. The purpose of the study was to determine the relationship between nurse therapeutic communication in the work phase and patient satisfaction with nursing services in the inpatient room at the DR.Drs.M.Hatta Bukittinggi Brain Hospital. The research design is a cross sectional study. The study population was all patients in the inpatient room at the Bukittinggi Brain Hospital. The sampling technique is quota sampling with a total of 67 people. The research instrument is a therapeutic communication questionnaire sheet and a patient satisfaction questionnaire sheet. The results showed that the patient stated that the nurse's therapeutic communication in the working phase was good (85.1%) and the patient stated that he was satisfied with the nursing services in the inpatient room, namely 82.1%. The results of the Spearman rank statistic test showed that there was a relationship between the therapeutic communication of nurses in the work phase and patient satisfaction with nursing services in the inpatient ward of the DR.Drs.M.Hatta Bukittinggi Brain Hospital with a p value of 0.000 < p value 0.05.